Numerical analysis of aluminium alloy gusset joints subjected to bending moment and axial force. (1st December 2017) - Xiong, Zhe; Guo, Xiaonong; Luo, Yongfeng; Xu, Han
Highlights: The numerical analysis program of the bending behaviour of AAG joints was presented. The FE models were accurately calibrated on the basis of the available test results. The FE models could describe the mechanical performance of AAG joints effectively. A four-line model was proposed to simulate the bending moment-rotation relationship. Parametric studies on the bending behaviour of AAG joints were investigated. Abstract: A test series was carried out and reported in a companion paper on the semi-rigid behaviour of aluminium alloy gusset (AAG) joints subjected to bending moment and axial force. This paper presented the results of an extensive numerical analysis program devoted to the investigation of the bending behaviour of AAG joints. The analysis was developed by means of finite element (FE) models implemented in the non-linear code ABAQUS. The procedure was accurately calibrated on the basis of the available experimental results. It is indicated that the FE models could be used effectively to describe the mechanical performance of AAG joints, including the failure modes, deformation process and bending moment-rotation curves. Furthermore, the shear connector, the thick plate and the advanced contact of bolts and bolt holes could improve the bending behaviour of AAG joints. According to the deformation process of AAG joints, a four-line model was proposed to simulate the bending moment-rotation relationship. To develop a further understanding, the effects of the member height, axial force, bolt pretension force, bolt gap and material nonlinearity on the bending behaviour of AAG joints were investigated.